2002
DOI: 10.1152/ajpregu.00419.2001
|View full text |Cite
|
Sign up to set email alerts
|

Glycerokinase activity in brown adipose tissue: a sympathetic regulation?

Abstract: The effect of brown adipose tissue (BAT) sympathetic hemidenervation on the activity of glycerokinase (GyK) was investigated in different physiological conditions. In rats fed a balanced diet, the activity of the enzyme was ∼50% lower in BAT-denervated pads than in intact, innervated pads. In rats adapted to a high-protein, carbohydrate-free diet, norepinephrine turnover rates and BAT GyK activity were already reduced, and BAT denervation resulted in a further decrease in the activity of the enzyme. Cold accli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 17 publications
6
28
1
1
Order By: Relevance
“…It was also found in this study that glyceroneogenic activity is even higher in rats adapted to the HP diet [7]. These animals have, in addition to low levels of BAT GyK [19], a reduced uptake and utilization of glucose [18], which we have shown to be due to the combined effects of low levels of insulin [20] and a reduced BAT sympathetic activity [8]. This raised the possibility that, because of the prolonged absence of carbohydrate in the diet of HP rats, the increase in glyceroneogenic activity represented a compensatory mechanism for the reduced production of G3P from glucose and glycerol, caused by the decreases in glycolysis and GyK activity.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…It was also found in this study that glyceroneogenic activity is even higher in rats adapted to the HP diet [7]. These animals have, in addition to low levels of BAT GyK [19], a reduced uptake and utilization of glucose [18], which we have shown to be due to the combined effects of low levels of insulin [20] and a reduced BAT sympathetic activity [8]. This raised the possibility that, because of the prolonged absence of carbohydrate in the diet of HP rats, the increase in glyceroneogenic activity represented a compensatory mechanism for the reduced production of G3P from glucose and glycerol, caused by the decreases in glycolysis and GyK activity.…”
Section: Introductionsupporting
confidence: 75%
“…From the results of previous studies, which included BAT hemidenervation experiments [12,19], we concluded that whereas GyK is under direct sympathetic control, BAT glyceroneogenic flux seems to be predominantly controlled by hormonal/metabolic factors. The available evidence strongly suggests that two factors are especially important: insulin and preformed fatty acids.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations